Molecular design and structural pecularities of the 3- and 4-pyridylboron-capped tris-glyoximate and tris-dichloroglyoximate iron(II) clathrochelates with apical donor groups. (1st March 2019) - Zelinskii, Genrikh E.; Belov, Alexander S.; Vologzhanina, Anna V.; Limarev, Ilya P.; Dorovatovskii, Pavel V.; Zubavichus, Yan V.; Lebed, Ekaterina G.; Voloshin, Yan Z.; Dedov, Alexey G.
Graphical abstract: Tris-glyoximate and tris-dichloroglyoximate iron(II) clathrochelates with apical donor pyridyl groups were obtained via template condensation and characterized by single crystal XRD. Their ligand aspect ratios were compared with those for the aliphatic macrobicyclic tris-dioximates. Abstract: Tris-glyoximate and tris-dichloroglyoximate iron(II) clathrochelates with apical pyridyl groups were obtained through one-pot template condensation of the corresponding α-dioxime with 3- or 4-pyridylboronic acids on the iron(II) ion as a matrix under vigorous reaction conditions using the boiling CF3 COOH as a solvent. The initially formed mixtures of mono- and diprotonated clathrochelate species were converted into the target macrobicyclic intracomplexes under basic conditions. These complexes were characterized using elemental analysis, MALDI-TOF mass spectrometry, IR, UV–Vis, 1 H and 13 C NMR spectroscopies, and by single crystal X-ray diffraction as well. In their molecules, the encapsulated iron(II) ion is situated in the center of its FeN6 -coordination polyhedron. The geometry of all the FeN6 -coordination polyhedra is intermediate between a trigonal prism and a trigonal antiprism with the average distortion angles φ from 16.7 to 17.7°. Their heights h fall from 2.36 to 2.38 Å and the averaged bite angles α vary in a narrow range 78.2–78.4°. Characteristic feature of the 3- and 4-pyridylboron-capped glyoximate clathrochelate molecules, as compared with their aliphatic and aromatic analogs, is shortening of the chelate CC bonds from 1.45 to 1.42 Å. Comparison of the values of a ligand aspect ratio for the obtained new pyridyl-terminated iron(II) clathrochelates with those for their known aliphatic tris-dioximate analogs was performed.